2016
DOI: 10.1017/gmh.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Mental health care in post-genocide Rwanda: evaluation of a program specializing in posttraumatic stress disorder and substance abuse

Abstract: BackgroundFollowing the genocide, millions of Rwandans are likely living with posttraumatic stress disorder (PTSD). Le Centre Psychothérapeutique Icyizere provides the only specialized treatment for PTSD in the Rwandan healthcare system.MethodsDemographics, diagnosis, treatment, outcomes, and scores on assessments of functioning and PTSD were recorded from clinical charts of all patients receiving care between October 2013 and 2014. Descriptive statistics and within-group t tests comparing functional impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…One of the underlying issues is that only 1 per cent of the national health budget is allocated to mental health needs [ 17 ]. Rugema, Krantz, Mogren, Ntaganira, and Persson [ 10 ] found that mental health services were underfinanced and described a situation in which “the total number of mental health nurses were 293 in 2012 and only two mental hospitals specialized in mental health care in Rwanda.” Additionally, it was found that as of 2014, no health centers within Rwanda had a quality assurance team or system to track mental health patient data [ 18 ]. However, enhancements to pre-existing programs such as the Rural Health Scale-Up National Strategic Plan have been initiated to address the need for mental health care in the country [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the underlying issues is that only 1 per cent of the national health budget is allocated to mental health needs [ 17 ]. Rugema, Krantz, Mogren, Ntaganira, and Persson [ 10 ] found that mental health services were underfinanced and described a situation in which “the total number of mental health nurses were 293 in 2012 and only two mental hospitals specialized in mental health care in Rwanda.” Additionally, it was found that as of 2014, no health centers within Rwanda had a quality assurance team or system to track mental health patient data [ 18 ]. However, enhancements to pre-existing programs such as the Rural Health Scale-Up National Strategic Plan have been initiated to address the need for mental health care in the country [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, retention was defined as number of substance use during the last 30 days or compliance with a treatment plan. Mason et al [34] assessed retention through self-reported numbers of days a person used substances, such as alcohol, cannabis, during the last month [35]; while in the Ng and Harerimana's study, [36] retention was determined by attendance to scheduled follow-up appointments. Retention was also operationalized as a period representing days on treatment from the first dose to the last dose of methadone or last date of the study period.…”
Section: Retention In the Addiction Recovery Processmentioning
confidence: 99%
“…In a one-year research on post-traumatic stress disorders and SUDs treatment, Ng and Harerimana, [36] highlighted the role of acknowledging people's beliefs about treatment and family involvement in improving retention outcomes. The research found a retention rate of 55.6% and attrition rate of 37.1% at one-year followup.…”
Section: Support From Family Relativesmentioning
confidence: 99%
See 1 more Smart Citation
“…With a population of approximately 12 million inhabitants, the country is currently undergoing a rapid economic development. The Rwandan government has invested heavily in delivery of quality health care, and physical health indicators have improved dramatically during the last decade [16]. However, there is still a scarcity of mental health professionals and most services are concentrated in the urban areas [17].…”
Section: Settingmentioning
confidence: 99%